Effectiveness of Medical Cannabis for the Treatment of Depression: A Naturalistic Outpatient Study - Specka, Michael; Bonnet, Udo; Schmidberg, Lisa; Wichmann, Julian; Keller, Martin; Scholze, Christian; Scherbaum, Norbert (Pharmacopsychiatry, 2024)
Background There is a lack of studies on the course and effectiveness of medical cannabis in the treatment of major depressive disorder (MDD).Methods Retrospective longitudinal (18 weeks) study of n=59 outpatients with MDD, treated with medical cannabis via a telemedical platform. Previous treatment with antidepressant medication was required for inclusion into the study. Standardized data collection was carried out at entry and during monthly consultations. Severity of depression was measured on a 0–10 point rating scale. Side-effects were assessed by a checklist.Results Patients were 20–54 years old; 72.9% were male; one third reported times of regular cannabis consumption within the previous five years. Drop-out rate was 22% after 18 weeks. Mean severity of depression decreased from 6.9 points (SD 1.5) at entry to 3.8 points (2.7) at week 18 (baseline observation carried forward; 95% CI for the mean difference: 2.4 to 3.8; p<0.001). A treatment response (>50% reduction of the initial score) was seen in 50.8% at week 18. One third of patients complained about side effects, none was considered as severe. Concomitant antidepressant medication (31% of patients) was not associated with outcome.Conclusions Medical cannabis was well tolerated and dropout rate was comparable to those in clinical trials of antidepressant medication. Patients reported a clinically significant reduction of depression severity. Further research on the effectiveness of medical cannabis for MDD seems warranted. Risks of this medication, such as sustaining or inducing a cannabis use disorder, or side effects such as poor concentration, must be taken into consideration.
Keywords: depression treatment; medical cannabis; THC; telemedicine; observational study